Estimating Contact Rates Between Metarhizium anisopliae–Exposed Males With Female Aedes aegypti - Reyes-Villanueva, Filiberto; Russell, Tanya L.; Rodríguez-Pérez, Mario A. (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction Effective control of Aedes aegypti will reduce the frequency and severity of outbreaks of dengue, chikungunya, and Zika; however, control programs are increasingly threatened by the rapid development of insecticide resistance. Thus, there is an urgent need for novel vector control tools, such as auto-dissemination of the entomopathogenic fungi Metarhizium anisopliae and Beauveria bassiana. The aim of this study was to estimate contact rates of M. anisopliae-exposed males with wild female Ae. aegypti. As a control the contact rates of untreated males with wild females was contrasted. Methods The study was conducted in Reynosa, Mexico. The treatment and control households (n = 15 per group) were geographically separated by an arid and hot area that naturally prevented the flight of males between arms. In each control household, 40 M. anisopliae-exposed male Ae. aegypti were released per week for 8 weeks (specimens were exposed to a concentration of 5.96 × 107 conidia/cm2 for 24 h; n = 4,800 males). In each control household, 40 untreated males were released per week for 8 weeks (n = 4,800 males). All specimens were dust-marked prior to release. Mosquito abundance was monitored with human landing collections, and captured Ae. aegypti were examined for any dust-marking. Results In the treatment households, the contact rate of Ae. aegypti females with marked, fungus-treated males was 14% (n = 29 females marked from 197). Where in the control households, the contact rate of females with marked, untreated males was only 6% (n = 22 marked from 365). In the treatment households the recapture rate of released males was at 5% and higher than that for the control households (which was 2%). Auto-dissemination of M. anisopliae from infected males to female Ae. aegypti was demonstrated through the recovery of an infected female from the floor of a household. Conclusions Overall, the contact rate between M. anisopliae-infected males with the natural female population was 60% higher than for the control group of healthy males. The results provide further support to the release of fungus-exposed males as a potentially useful strategy against Ae. aegypti, though further research is required.